Large-area solution-processable black phosphorus for electronic application - Zhen Zhong; Xiuduan Gong; Haihong Wei; Haoran Mu; Jian Yuan (Materials Letters: X, 2024)
Two-dimensional (2D) layered black phosphorus (BP), with a direct band gap and high carrier mobility, has shown great potential for next generation electronics and optoelectronics. However, how to prepare a large-area 2D material film is still a big problem for realizing its practical applications. Herein, an improved one-step solution-processable method is put forward to solving this problem to get uniform and large-area BP film. Our results show that the designed electrodes can be fully covered by BP flakes and the corresponding FET reveals relatively high performance. Our study opens a new avenue in fabricating large-area ultra-thin BP films.